Pragmatism or idealism: a systematic review and visual analysis of Winnicott’s psychoanalytical treatment views - Xie, Zhengyan; Yan, Yuting; Peng, Kejuan (Frontiers in Psychiatry, 2023)
Winnicott is an outstanding representative of the School of Object Relations, and his unique psychoanalytic treatment views have been greatly influential to the psychoanalytical community. Winnicott emphasizes the impact of facilitating environment and the key role of the maternal-child relationship in the early psychological growth of individuals. He puts forward the ideas of the development mechanism of the true self and the false self, which builds a bridge between the characteristics of adult psychopathology and the characteristics of early maternal-child relationships, providing a new perspective for research on individual self-development and psychoanalysis. Winnicott creatively introduces the concepts of the transitional object and the transitional phenomena into the theories of Object Relations. He relates the transitional experience to the field of mental health, and extends it from the relationship between the mother and the child to adult life, which not only has had a revolutionary impact on modern psychoanalysis but also literature, aesthetics, and other fields. Winnicott highlights the importance of the patient's emotional development in the treatment. He advocates holding the patients' sentiments and meeting their emotional needs. He also approves of the emotional reparenting of the patients, to make them gain the ability to establish a relationship with the real world. His treatment views formed through a large number of clinical practices are very practical and full of humanistic care. This review summarizes Winnicott's psychoanalytical treatment views as well as his marvelous original concepts, and analyzes the hot topics of academic research on his theories based on a visualization analysis by using the software CiteSpace, which includes data in the Web of Science Core Collection published from 1978 to 2023 with 365 papers involved. The study provides a macroscopic and panoramic review of Winnicott's theories, and it clearly shows Winnicott's significant influence on the field of psychoanalysis and related fields.